Effect of sacubitril/valsartan versus enalapril on glycaemic control in patients with heart failure and diabetes: a post-hoc analysis from the PARADIGM-HF trial - Seferovic, Jelena P; Claggett, Brian; Seidelmann, Sara B; Seely, Ellen W; Packer, Milton; Zile, Michael R; Rouleau, Jean L; Swedberg, Karl; Lefkowitz, Martin; Shi, Victor C; Desai, Akshay S; McMurray, John J V; et al. (The lancet. Diabetes & endocrinology, 2017)
Diabetes is an independent risk factor for heart failure progression. Sacubitril/valsartan, a combination angiotensin receptor-neprilysin inhibitor, improves morbidity and mortality in patients with heart failure with reduced ejection fraction (HFrEF), compared with the angiotensin-converting enzyme inhibitor enalapril, and improves peripheral insulin sensitivity in obese hypertensive patients. We aimed to investigate the effect of sacubitril/valsartan versus enalapril on HbA1c and time to first-time initiation of insulin or oral antihyperglycaemic drugs in patients with diabetes and HFrEF. In a post-hoc analysis of the PARADIGM-HF trial, we included 3778 patients with known diabetes or an HbA1c ≥6·5% at screening out of 8399 patients with HFrEF who were randomly assigned to treatment with sacubitril/valsartan or enalapril. Of these patients, most (98%) had type 2 diabetes. We assessed changes in HbA1c, triglycerides, HDL cholesterol and BMI in a mixed effects longitudinal analysis model. Time to initiation of oral antihyperglycaemic drugs or insulin in subjects previously not treated with these agents were compared between treatment groups. There were no significant differences in HbA1c concentrations between randomised groups at screening. During the first year of follow-up, HbA1c concentrations decreased by 0·16% (SD 1·40) in the enalapril group and 0·26% (SD 1·25) in the sacubitril/valsartan group (between-group reduction 0·13%, 95% CI 0·05–0·22, p=0·0023). HbA1c concentrations were persistently lower in the sacubitril/valsartan group than in the enalapril group over the 3-year follow-up (between-group reduction 0·14%, 95% CI 0·06–0·23, p=0·0055). New use of insulin was 29% lower in patients receiving sacubitril/valsartan (114 [7%] patients) compared with patients receiving enalapril (153 [10%]; hazard ratio 0·71, 95% CI 0·56–0·90, p=0·0052). Similarly, fewer patients were started on oral antihyperglycaemic therapy (0·77, 0·58–1·02, p=0·073) in the sacubitril/valsartan group. Patients with diabetes and HFrEF enrolled in PARADIGM-HF who received sacubitril/valsartan had a greater long-term reduction in HbA1c than those receiving enalapril. These data suggest that sacubitril/valsartan might enhance glycaemic control in patients with diabetes and HFrEF. Novartis.